'Let us be cool, calm—and elected': conservative party strategy and political narrative prior to the 1983 general election. Issue 3 (3rd July 2018) - Abernethy, Sally
ABSTRACT: The 1983 general election saw the Conservative party under Margaret Thatcher achieve a decisive victory. The result provided a mandate to continue with a radical economic programme that, two years earlier, was so unpopular it led to the lowest approval ratings of any government or Prime Minister on record. Yet, rather than altering the substance of their programme, the Conservatives had instead sought to improve the public perception of their objectives. The construction and propagation of a compelling political 'narrative' played a key role in this. This article evaluates the construction of this Conservative strategy.